Assessment of corroded prestressed and posttensioned concrete structures: A review. (17th June 2021) - Vereecken, Eline; Botte, Wouter; Lombaert, Geert; Caspeele, Robby
Abstract: Prestressed structures are commonly used all over the world. They might be subjected to degradation, such as corrosion of the prestressing steel. This can influence the resistance of these structures and induce early failure. Hence, prediction of the corrosion level is important in the assessment of existing prestressed structures. For this purpose, the corrosion process and the accompanying influences on the structure should be modeled. For reinforced concrete (RC) structures, a lot of research and guidelines are available to model the corrosion process. Nevertheless, this corrosion process might differ for prestressed structures, due to the different structural composition, the different geometry of the strands or tendons compared with reinforcement bars, the presence of the prestress, and so on. Moreover, for posttensioned structures, initiation and propagation of corrosion are even more different from corrosion in RC structures, due to the location of the steel in ducts and the lack of direct contact with the surrounding concrete. In this paper, a state‐of‐the‐art on the assessment of prestressed and posttensioned structures subjected to corrosion is given based on a literature review. Different models for the corrosion process and their influence on the structure are discussed. Comparison is made between reinforced, prestressed, and posttensioned structures. Furthermore, some assessment procedures are indicated and relevant topics for further research are given.